Implementation of Local Wisdom Based Learning in Realizing Pancasila Student Profiles in Elementary Schools - Umar Seno; Sabar Narimo; Djalal Fuadi; Minsih; Choiriyah Widyasari (Jurnal Ilmiah Sekolah Dasar, 2022)
Learning based on local wisdom is a breakthrough in the world of education in realizing the profile of Pancasila students. This study aimed to analyze the implementation of local wisdom-based learning in elementary schools to recognize the shape of Pancasila students. The method in this study uses a qualitative approach with an exploratory, descriptive design. The subjects in this study included students and teachers at an elementary school. Data collection techniques used are observation and interviews. Data analysis techniques include reduction, data display, and data verification. Test the validity of the data using technical triangulation. The results showed that the achievement of implementing local wisdom-based learning in one of the elementary schools was the achievement of competency selection of more than 90%. Choice in the formulation of indicators of less than 75%. Selection of learning materials above 90%. The formulation of learning objectives is less than 75%. Use of learning resources above 90%. Use of learning media above 90%. The use of learning activities is above 85%. Use of ratings above 85%. It is hoped that the teacher will pay more attention to selecting the formulation of learning objectives and the formulation of indicators so that the embodiment of the Pancasila student profile can be carried out more proportionally and comprehensively.